Two New Pests of Khasi Pine, Pinus kesiya Royle Ex Gordon - Singh, Pratap; Singh, Raghubir (Indian Forester, 1978)
The defoliation epidemics in the khasi pine forests of Jaintia Hills and Khasi Hill, Meghalaya were studied. The insects responsible for the epidemics were Eterusia pulchella and Dichocrocis puncliferalis. Both the insects are polyphagous and reported for the first time as defoliators of khasi pine E. pulchella is distrihuted all along the Himalayas while D. puncliferalis is widely distributed all over south east Asia including India. Egg, larva, pupa and adult of the species are described and notes on their biology given. Both these insects are potential threat to Pinus kesiya in the region.